2000
DOI: 10.1002/(sici)1099-1379(200006)21:4<443::aid-job24>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Organizational antecedents and outcomes of job insecurity: a longitudinal study in three organizations in Finland

Abstract: The aim of the study was to examine perceived job insecurity and its organizational antecedents and outcomes within a one-year time period. The study was carried out by means of questionnaires, which were responded to twice, in 1995 (Time 1) and 1996 (Time 2), by employees in three organizations: a factory, a bank, and a municipal social and health care department. The present article is based on the data of those employees (n 210) who participated in the study in both years. The results indicated that perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 24 publications
(42 reference statements)
7
89
0
7
Order By: Relevance
“…Low levels of job security may also exert dysfunctional effects on an employee's job performance through reduced motivation at work (Loi, Ngo, Zhang, & Lau, 2011). For example, Kinnunen, Mauno, Natti, and Happonen (2000) argue that employees who are worried about losing their jobs exert less effort at work. The dysfunctional effects resulting from low levels of job security have also been widely investigated in the literature (Sverke, Hellgren, & Näswall, 2002).…”
Section: The Mediating Effects Of Job Securitymentioning
confidence: 99%
“…Low levels of job security may also exert dysfunctional effects on an employee's job performance through reduced motivation at work (Loi, Ngo, Zhang, & Lau, 2011). For example, Kinnunen, Mauno, Natti, and Happonen (2000) argue that employees who are worried about losing their jobs exert less effort at work. The dysfunctional effects resulting from low levels of job security have also been widely investigated in the literature (Sverke, Hellgren, & Näswall, 2002).…”
Section: The Mediating Effects Of Job Securitymentioning
confidence: 99%
“…This, in turn, results in lower levels of organisational commitment by the workforce especially when associated with feelings of inequity about the restructuring process [31]. Unsurprisingly, job satisfaction levels tend to fall and social relationships among colleagues and with superiors deteriorate [32]; this may manifest as higher levels of bullying and harassment. The evidence relating to performance is more equivocal though the impact of restructuring is generally negative; in a minority of studies productivity was found to rise but, even here, the quality of work was lower [33].…”
Section: Managing Changementioning
confidence: 99%
“…Job insecurity, in turn, predicted organizational commitment, perceived performance, perceived organizational support, and intention to quit, consistent with the literature. Kinnunen, Mauno, Natti, and Happonen (2000), in a study of antecedents and outcomes of job insecurity in three organizations in Finland, found that gender and organization were significant predictors of job insecurity. The present study builds on the existing literature by measuring job insecurity as a multidimensional construct and by examining job insecurity during a crisis in an organization as opposed to during a period of organizational stability, as is often the case (cf.…”
mentioning
confidence: 99%